Public-private partnership on the provision of school facilities in Tigbauan National High School in the province of Iloilo - Galvan, Joy T.
This research project aims to determine the reason why public and private sectors engage in partnership on the provision of school facilities and to determine the strategies of public-private organizations, engaged in partnerships.